The Dream Job of Generation Z Youth - Nimphatomwong, Pawinee; Kangsadanporn, Assist.Prof.Dr. Apirat (Journal of Dhamma for Life, 2023)
The purpose of this research is to 1) study the lifestyle or behaviour of Generation Z youth, 2) explore the desired professions of Generation Z youth and 3) investigate the factors influencing the career choices of Generation Z youth. This research is quantitative research, employing in-depth interviews with 15 key youth informants, consisting of 5 males, 5 females, and 5 LGBTQ all of whom are in Generation Z. This research is conducted using semi-structured interviews and analysing the information to address all three research objectives. The findings reveal that Generation Z youth share common lifestyle patterns. They are high school students who attend classes from Monday to Friday. They tend to engage in personal activities, homework, sports, relaxation, and reading after school. On weekends, they typically go on trips, shopping, travel to different provinces, stay at home playing games, or participate in activities they enjoy. As for their study time, they usually manage their time according to their preference and appropriateness. Yet, some find their lifestyle to be quite monotonous due to the heavy academic workload and wish for more relaxation time. As for their dream career, Generation Z youth are interested in various fields, ranging from a doctor, pharmacists, tutors, air hostesses, psychiatrists, psychologists, financial analysts, professional athletes, novelists, and online entrepreneurs, to YouTubers. The key factors influencing career choices include income, societal values, self-confidence, aptitude, personal interests, staying informed, and technological advancements. Moreover, it found that influencers influencing the career choices of Generation Z youth tend to be more symbolic rather than repetitive and prescriptive.